On Debugging Non-Answers in Keyword Search Systems - Baid, Akanksha; Wu, Wentao; Sun, Chong; Doan, AnHai; Naughton, Jeffrey F. (Proceedings of the 18th International Conference on Extending Database Technology (EDBT 2015), 2015)
Handling non-answers is desirable in information retrieval systems. Current e-commerce websites usually try to suppress the somewhat dreaded message that no results have been found. Possible solutions include, for example, augmenting the data with synonyms and common misspellings based on query logs. Nonetheless, this is only achievable if we can know the cause of the non-answers. Under the hood, most e-commerce data sits in some structured format. Debugging non-answers in the underlying KWS-S systems is therefore not trivial—non-answers in a KWS-S system could be a problem of the data (e.g., absence of some keywords), the schema (e.g., missing key-foreign-key joins), or due to empty join results from one of possibly several joins in the generated SQL queries. So far, we are unaware of any previous work that explores how to enable developers to debug non-answers in a KWS-S system. In this paper, we take a first step towards this direction by proposing a KWS-S system that can expose non-answers to the developers. Our system presents the developers with the maximal nonempty sub-queries that represent the frontier cause of the non-answers. We outline the challenges in building such a system and propose a lattice structure for efficient exploration of the non-answer query space. We also evaluate our proposed mechanisms over a real world dataset to demonstrate their feasibility.